The Impact of E-Government Implementation Through the Sentuh Tanahku Application on the Quality of Public Services at the Sidenreng Rappang Regency Land Office - Ahniar Achmad; Haryanti Hamid; Kamaruddin Sellang (Global Writing Academica Researching and Publishing, 2026)
This study aims to analyze the implementation of e-government through the Sentuh Tanahku application and to determine its effect on the quality of public services at the Land Office of Sidenreng Rappang Regency. This research is motivated by the utilization of digital technology in land services through the Sentuh Tanahku application as a form of e-government implementation aimed at improving the effectiveness, efficiency, and quality of public services. This study employed a quantitative method with a descriptive and verificative approach. The population consisted of 170 verified users of the Sentuh Tanahku application, with a sample of 63 respondents. The sample was determined using the Slovin formula and purposive sampling technique. Data were collected through observation, questionnaires, and literature review. The collected data were then analyzed using descriptive statistics and simple linear regression with the assistance of IBM SPSS Statistics 21. The results showed that the implementation of e-government through the Sentuh Tanahku application was categorized as good, with a percentage of 73.4%. This finding indicates that the aspects of support, capacity, and value had been implemented well in supporting the provision of public services at the Land Office of Sidenreng Rappang Regency. Furthermore, the results of the simple linear regression analysis showed that the implementation of e-government through the Sentuh Tanahku application had a positive and significant effect on the quality of public services. The coefficient of determination (R Square) was 0.459, indicating that the implementation of e-government contributed 45.9% to the quality of public services, while the remaining 54.1% was influenced by other factors not examined in this study. The t-test results showed a t-value of 7.196 with a significance level of 0.000 (< 0.05), indicating that the research hypothesis was accepted. Therefore, it can be concluded that the implementation of e-government through the Sentuh Tanahku application has been carried out well and has a significant effect on improving the quality of public services at the Land Office of Sidenreng Rappang Regency.